Roadmap zur ökonomischen Analyse von E-Health Anwendungen - Stefan Müller-Mielitz; Thomas Lux; Juliane Köberlein-Neu; Uwe Fachinger (University of Wuppertal, Schumpeter School of Business and Economics, 2021)
E-health interventions are considered an important success factor in the continuous improvement of healthcare both nationally and internationally. Particularly in integrated care arrangements, they are an important infrastructural element. Of course, when developing new interventions and introducing them into the healthcare system, health economic evaluations (HEEs) are mandatory. From a healthcare organizational as well as governmental view, it is especially important that interventions are cost-effective and affordable. Consequently, there is a growing interest in studying digital intervention's implications on healthcare costs. In order to enable a standardized procedure, the working group "E-Health" of the German Society for Health Economics has begun to develop a roadmap for the health economic evaluation of e-health interventions, which complements current recommendations that exist for Germany.
urn:nbn:de:hbz:468-20210826-104728-2
Keywords: 330; e-Health; health economic evaluation